2019
DOI: 10.1007/s13201-019-1060-3
|View full text |Cite
|
Sign up to set email alerts
|

Error analysis of adsorption isotherm models for penicillin G onto magnesium oxide nanoparticles

Abstract: The adsorption of penicillin G (PC-G) from aqueous solution by magnesium oxide (MgO) nanoparticles has been investigated. This experimental study was conducted in a laboratory scale. The effects of various operating parameters such as pH (3-11), the dosage of MgO nanoparticles (0.3-1.5 g/L), contact time (20-150 min), and concentration of PC-G (50-200 mg/L) were studied. The results showed that under optimal conditions of concentration of 50 mg/L, pH 3, MgO nanoparticles dosage of 1.5 g/L and contact time of 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Recently, various nanocatalysts were used for antibiotics removal. [16][17][18][19][20] In this technique, some advantages such as higher efficiency, there is a selectivity to nontoxic produces, requiring relatively slight conditions, and more comfortable operation comparing to other biological and physicochemical methods. [21][22][23] For developing selective and efficient nanocatalysts, different materials have been used for antibiotics removal.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, various nanocatalysts were used for antibiotics removal. [16][17][18][19][20] In this technique, some advantages such as higher efficiency, there is a selectivity to nontoxic produces, requiring relatively slight conditions, and more comfortable operation comparing to other biological and physicochemical methods. [21][22][23] For developing selective and efficient nanocatalysts, different materials have been used for antibiotics removal.…”
Section: Introductionmentioning
confidence: 99%
“…Since magnesium oxide (MgO), titanium dioxide (TiO 2 ), aluminum oxide (Al 2 O 3 ), and zinc oxide (ZnO) have a high specific surface area by themselves, the specific surface area of prepared materials by those metal oxides have higher specific surface area than raw material. Moreover, the previous studies reported the specific surface area of MgO, TiO 2 , Al 2 O 3 , and ZnO were 60, 50, 40, and 30 m 2 /g, and they could be arranged in order from high to low of MgO > TiO 2 > Al 2 O 3 > ZnO 30 , 31 . As a result, it could support why SBBM had a higher surface area than other materials.…”
Section: Resultsmentioning
confidence: 88%
“…18, whereas, Pseudo 1st order con rms physical adsorption. (Rahdar et al 2019) also performed the datasets into the kinetic study i.e., two models. In this study, Pseudo 2nd order tted the best.…”
Section: Pseudo-rst-order Modelmentioning
confidence: 99%